2007
DOI: 10.1152/ajpheart.01141.2006
|View full text |Cite
|
Sign up to set email alerts
|

Possible usefulness of apocynin, an NADPH oxidase inhibitor, for nitrate tolerance: prevention of NO donor-induced endothelial cell abnormalities

Abstract: The long-term benefits of nitroglycerin therapy are limited by tolerance development. Understanding the precise nature of mechanisms underlying nitroglycerin-induced endothelial cell dysfunction may provide new strategies to prevent tolerance development. In this line, we tested interventions to prevent endothelial dysfunction in the setting of nitrate tolerance. When bovine aortic endothelial cells (BAECs) were continuously treated with nitric oxide (NO) donors, including nitroglycerin, over 2-3 days, basal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
0
16
0
2
Order By: Relevance
“…BH 4 levels are upregulated by H 2 O 2 -mediated induction of GTP cyclohydrolase (36,37), and we speculate that dismutation of superoxide to H 2 O 2 by rhSOD may account for the increase in BH 4 (15). Conversely, apocynin inhibits superoxide generation by NADPH oxidase and has been reported to scavenge H 2 O 2 in vitro (17,19). Ventilation with NO also reduced superoxide levels in PPHN PA but had less pronounced effects on eNOS expression and did not affect BH 4 or BH 2 levels (15).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…BH 4 levels are upregulated by H 2 O 2 -mediated induction of GTP cyclohydrolase (36,37), and we speculate that dismutation of superoxide to H 2 O 2 by rhSOD may account for the increase in BH 4 (15). Conversely, apocynin inhibits superoxide generation by NADPH oxidase and has been reported to scavenge H 2 O 2 in vitro (17,19). Ventilation with NO also reduced superoxide levels in PPHN PA but had less pronounced effects on eNOS expression and did not affect BH 4 or BH 2 levels (15).…”
Section: Discussionmentioning
confidence: 80%
“…The dose of apocynin was calculated with the assumption of an immediate volume of distribution of fetal lung liquid volume (ϳ20 -30 ml/kg) (33) and a target concentration of 0.5-1 mM in the lung liquid. This concentration has been shown to be effective in various cell studies (17,19). We chose the intratracheal route because of our prior success with intratracheal rhSOD (24) and because we wished to induce selective pulmonary vasodilation without systemic hypotension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, data obtained with apocynin, a polyphenols structural analogue, reported by Fukatsu et al (2007) indicated that this compound, pharmacologically known to be able to prevent the increase in protein expression of NADPH oxidase, a source of superoxide anions, could be a means of protection against nitrate tolerance.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, because of the development of tolerance to NO donors such as nitroglycerin, their long-term use would be difficult as we described elsewhere. 82 We investigated cellular senescence in human aorta obtained by autopsy and in HUVEC. 72 We demonstrated cellular senescence with SA-b-gal-positive staining in atherosclerotic lesions of the luminal side of human thoracic aorta.…”
Section: Relationship Between Endothelial Cell Senescence and Nomentioning
confidence: 99%